A detailed investigation of the relaxor like dielectric behaviour of the sr1—xlaxti1—xcoxo3 system - Upadhyay S.; Kumar D.; Parkash O. (My University, 2025)
A few compositions in the valence compensated perovskite system Sr1—xLaxTi1—xCoxO3 have been reported to show relaxor like dielectric behaviour. In order to thoroughly investigate this relaxor like behaviour, a few more compositions in this system with 0.20 < x < 0.40 have been prepared by solid state ceramic method and characterized. All the compositions are single phase solid solution having cubic crystal structure. The microstructure and dielectric behaviour depend on composition. Complex plane impedance and modulus analysis of the electrical data have been made to study the origin of relaxor like behaviour. © 1997 Taylor and Francis Group, LLC.